Bridging a sensory gap between deaf and hearing people–A plea for a situated design approach to sensory augmentation - Witter, Michel; de Rooij, Alwin; van Dartel, Michel; Krahmer, Emiel (Frontiers in Computer Science, 2022)
Deaf and hearing people can encounter challenges when communicating with one another in everyday situations. Although problems in verbal communication are often seen as the main cause, such challenges may also result from sensory differences between deaf and hearing people and their impact on individual understandings of the world. That is, challenges arising from a sensory gap. Proposals for innovative communication technologies to address this have been met with criticism by the deaf community. They are mostly designed to enhance deaf people’s understanding of the verbal cues that hearing people rely on, but omit many critical sensory signals that deaf people rely on to understand (others in) their environment and to which hearing people are not tuned to. In this perspective paper, sensory augmentation technologically, extending people’s sensory capabilities, is put forward as a way to bridge this sensory gap: 1) by tuning to the signals deaf people rely on more strongly but are commonly missed by hearing people, and vice versa, and 2) by sensory augmentations that enable deaf and hearing people to sense signals that neither person is able to normally sense. Usability and user-acceptance challenges, however, lie ahead of realizing the alleged potential of sensory augmentation for bridging the sensory gap between deaf and hearing people. Addressing these requires a novel approach to how such technologies are designed. We contend this requires a situated design approach.